2016
DOI: 10.1176/appi.ajp.2016.15111381
|View full text |Cite
|
Sign up to set email alerts
|

Heritable and Nonheritable Pathways to Early Callous-Unemotional Behaviors

Abstract: Objective Callous-unemotional behaviors in early childhood identify children at high risk for severe trajectories of antisocial behavior and callous-unemotional traits that culminate in later diagnoses of conduct disorder, antisocial personality disorder, and psychopathy. Studies have demonstrated high heritability of callous-unemotional traits, but little research has examined specific heritable pathways to earlier callous-unemotional behaviors. Additionally, studies indicate that positive parenting protects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
143
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 41 publications
13
143
3
1
Order By: Relevance
“…We found that the genetic and environmental influences on multiple relevant behaviors (the ASPD criteria) are statistically associated rather than independent. This aligns with the observations that full-blown psychopathy usually involves both genetic and environmental exposures (Derefinko & Widiger 2016; Hyde et al 2016; Viding & McCrory 2012). However, another study has reported statistically independent genetic and environmental factors, as discussed next.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the genetic and environmental influences on multiple relevant behaviors (the ASPD criteria) are statistically associated rather than independent. This aligns with the observations that full-blown psychopathy usually involves both genetic and environmental exposures (Derefinko & Widiger 2016; Hyde et al 2016; Viding & McCrory 2012). However, another study has reported statistically independent genetic and environmental factors, as discussed next.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings have implications for nosology (Livesley 2005; Kendler 2006), psychometrics (Livesley 2005; Franić et al 2013), molecular genetics (Tielbeek et al 2012; Salvatore et al 2015), developmental psychopathology (Hyde et al 2016; Viding & McCory, 2012), and human behavioral ecology and evolution (Nettle et al 2013; Ribeiro da Silva et al 2015; Del Giudice et al 2011; Colman & Wilson, 1997; Ellis 1988). Our study is relevant to all these research fields in providing evidence that a unidimensional ASPD phenotype exists and permeates the domains of genetic and environmental influences.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, we cannot exclude potential gene-environment correlations (62). Future studies using genetically-informed designs (63) may be able to parse heritable and non-heritable effects from pathways linking adversity to neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, consistent with other recent findings from the early childhood period, our results highlight that measuring CU behaviors as young as three years-old may help to identify children at heightened risk for behavior problems across childhood (see Waller, Shaw et al, 2015). These children and their families are likely to benefit from early-starting interventions that help reduce risk for aggression by increasing positive parenting, and improving parent-child cooperation and engagement (e.g., Hyde et al, 2016). Evidence to date suggests that parent-focused interventions implemented via regular contact with families in their communities, and that improve social support and increase motivation for change, can be effective at engaging families and reducing behavior problems even among children with high CU behaviors (Dishion et al, 2008; Hyde et al, 2013; Waller, Gardner, & Hyde, 2013).…”
Section: Discussionmentioning
confidence: 99%